TYPES AND MARKERS OF POLITENESS DEPICTED IN PUBLIC SERVICE ADVERTISEMENT IN PEKANBARU - Muhammad Indra Gunawan; Aprizawati Aprizawati Aprizawati (INOVISH JOURNAL, 2018)
The application of politeness can be found in daily life through behavior of deeds and words, it also can describes in a public service advertisement. The purpose of this research is to determine and explaine the types and markers of politeness depicted in Public Service Advertisement in Pekanbaru. This research is done chronologically based on three steps, they are; collecting of the data, analysis of the data and presenting the result analysis that is guided by methods and various techniques of language analysis. The data are collecting by observational method. Tap technique is used as the basic technique. In observing the data, pictures of the data are documented by using camera tool of observation. Besides, note-talking technique is also used in documenting the data. Data collected then is analyzed by using pragmatic identity method. The result of the analysis then is presented by using informal method. From the results of analysis, there found eights types of politeness that are applied in Public Service Advertisement in Pekanbaru. Related to politeness markers used in Public Service Advertisement in Pekanbaru there found three politeness markers. Those three are; mari, ayo and –lah.Keywords:          Types and markers, politeness depicted, public services, advertisement.